Feasibility and Acceptability of Light Therapy to Reduce Fatigue in Adolescents and Young Adults Receiving Cancer-Directed Therapy. Issue 4 (4th July 2021) - Crabtree, Valerie McLaughlin; LaRosa, Kayla N.; MacArthur, Erin; Russell, Kathryn; Wang, Fang; Zhang, Hui; Pan, Haitao; Brigden, Jane; Schwartz, Laura E.; Wilson, Matthew; Pappo, Alberto
ABSTRACT: Objective/Background: Fatigue is one of the most consistent and distressing symptoms reported by adolescent/young adult (AYA) oncology patients. Bright white light (BWL) is used to treat fatigue in adult oncology but has not been explored in AYA oncology patients. The purpose of the current study was to determine the feasibility and acceptability of BWL for AYA who were receiving cancer-directed therapy. Participants: 51 AYA patients with newly diagnosed solid tumors, including lymphoma. Methods: Participants were randomized to dim red light (DRL, n = 25) or BWL (n = 26) from devices retrofitted with adherence monitors for 30 minutes upon awakening daily for 8 weeks. Side effects were assessed via modified Systematic Assessment for Treatment-Emergent Effects (SAFTEE). Participants completed the PedsQL Multidimensional Fatigue Scale. Results: Of patients approached, 73% consented and participated. Mean adherence was 57% of days on study with 30.68 average daily minutes of usage. BWL did not cause more extreme treatment-emergent effects over DRL. Patients in the BWL group demonstrated significant improvement on all fatigue outcomes by both self-report and parent proxy report, which was not observed in the DRL group. Conclusions: This is the first study to evaluate the feasibility and acceptability of light therapy to reduce fatigue in AYA patients receiving cancer-directed therapy. These findings demonstrate the feasibility and acceptability of the intervention and provide preliminary evidence of the potential benefits of BWL, which warrants further study in a confirmatory efficacy trial. ClinicalTrials.gov Identifier Number: NCT02429063